Improved survival in adolescents and young adults (AYA) patients aged 14–55 years with acute lymphoblastic leukemia using pediatric-inspired protocol – a retrospective analysis of a real-world experience in 79 of patients treated at a national tertiary care referral center. (2021) - Hanbali, Amr; Kotb, Ahmed; Fakih, Riad El; Alfraih, Feras; Ahmed, Syed Osman; Shaheen, Marwan; Alhayli, Saud; Alahmari, Ali; Alotaibi, Ahmad; Alshaibani, Alfadel; Riash, Mahmoud Abu; Deeba, Farah; et al.
Abstract: Background: Treating adolescents and young adults (AYA) patients with acute lymphoblastic leukemia (ALL) using pediatric-inspired protocols have shown improvement in outcomes. Most data available in the literature of such protocols is derived from well-controlled clinical trials. This report aims to provide a real-world experience from using a pediatric-inspired protocol in ALL-AYA population in larger number of patients treated at a national tertiary care referral center. Methods: Newly diagnosed Philadelphia negative ALL-AYA patients ages between 14 and 55 years of age were treated on an institutional protocol (AYA-15 protocol) adopted from a modified version of Children's Cancer Group (CCG) 1900 protocol. At the time of this publication, a total of 79 patients were treated using the AYA-15 protocol between 2015 and 2020). Event-free survival (FFS), disease-free survival (DFS), and overall survival (OS) were analyzed using cumulative incidence and Kaplan-Meier methods. Results: The median age at diagnosis was 18 years (14–51 years) with 63% male patients. Complete remission (CR) at day 28 of induction was achieved in 88.6% of which 73.4% were minimal residual disease (MRD) negative. At a median follow up of 5 years, EFS, DFS and OS were 57.5%, 69.2% and 75.8% respectively. Toxicities were within the expected range with infections and transaminitis being the most common adverse events. Conclusion: Our single-center experience real-world data in treating AYA-ALL patients with pediatric-inspired protocol demonstrates encouraging results of high survival rate and excellent tolerability for patients aged 18–55 years.